Hindu nationalism : a reader - Jaffrelot, Christophe (Princeton University Press, 2007)
"Hindu nationalism came to world attention in 1998, when the Hindu nationalist Bharatiya Janata Party (BJP) won national elections in India. Although the BJP was defeated nationally in 2004, it continues to govern large Indian states, and the movement it represents remains a major force in the world's largest democracy. This book presents the thought of the founding fathers and key intellectual leaders of Hindu nationalism from the time of the British Raj, through the independence period, to the present. Spanning more than 130 years of Indian history and including the writings of both famous and unknown ideologues, this reader reveals how the "Hindutuva" movement approaches key issues of Indian politics. Covering such important topics as secularism, religious conversion, relations with Muslims, education, and Hindu identity in the growing diaspora, this reader will be indispensable for anyone wishing to understand contemporary Indian politics, society, culture, or history."--Book cover